Analisis Permintaan Pangan di Kawasan Timur Indonesia - Handewi P.S. Saliem (Jurnal Agro Ekonomi, 2002)
EnglishThe research was aimed to study the demand for food in the Eastern Region of Indonesia (ERI). The study used the 1996 National Socio-Economic Survey (SUSENAS) data collected by the Central Bureau of Statistics (Biro Pusat Statistik). Descriptive method is used for studying consumption pattern and Linear Approximation Almost Ideal Demand System (LA/AIDS) is used for analyzing food demand. Result of the study show as follows: (1) rice is dominant in structure of household budget, energy contribution and household protein in ERI: (2) in some provinces of ERI, there was shifting in consumption pattern of staple food from non-rice to rice between 1976 and 1996; (3) consumption of food as source of carbohydrate in rural areas is higher than in urban areas, but it was vice versa for the consumption of food as protein sources; ( 4) the higher income of household, the higher food consumption; (5) food demands of household in rural areas was more responsive to price and income changes than the household in urban areas, and households with the higher income were less responsive to the price and income changes; and (6) variable of number of household member and education level of head of household influenced significantly to food demand of household in RI. Implication of the study are (1) it is necessary to develop and promote non-rice main food that is suitable to local potentials; (2) policies of food and nutrition in ERI should be prioritized to the household with lower income in rural areas; (3) to satisfy consumption level of energy and protein is needed to increase about 2% income of households with lower income in rural areas; and (4) socialization of education and extension of food and nutrition are still very important carried out in ERI.IndonesianPenelitian ini bertujuan untuk mempelajari pola konsumsi dan permintaan pangan di wilayah Kawasan Timur Indonesia (KTI) dengan menggunakan data Survei Sosial Ekonomi Nasional (Susenas) tahun 1996 yang dikumpulkan oleh Biro Pusat Statistik (BPS). Metoda deskriptif digunakan untuk mempelajari pola konsumsi, sedangkan untuk menganalisis permintaan pangan digunakan alat analisis ekonometrika sistem persamaan permintaan "linear approximation almost ideal demand system" (LA/AIDS). Hasil penelitian menunjukkan bahwa: (1) Beras dominan dalam struktur anggaran, kontribusi energi dan protein rumah tangga di KTI, (2) Di berbagai provinsi di KTI antara 1979-1996 telah terjadi pergeseran dari pola pangan pokok non beras ke arah pola pangan pokok beras, (3) Konsumsi pangan sumber karbohidrat di daerah pedesaan KTI lebih tinggi dari pada di kota, namun untuk pangan sumber protein terjadi hal sebaliknya, (4) Makin tinggi tingkat pendapatan makin tinggi tingkat konsumsi pangan, (5) Permintaan pangan rumah tangga di pedesaan KTI lebih responsif terhadap perubahan harga dan pendapatan dibanding rumah tangga di kota, dan makin tinggi tingkat pendapatan makin kurang responsif terhadap perubahan harga dan pendapatan, (6) Peubah jumlah anggota rumah tangga dan pendidikan kepala rumah tangga berpengaruh nyata terhadap permintaan pangan rumah tangga di KTI. lmplikasi dari temuan hasil studi ini adalah: (1) Perlunya digalakkan pengembangan dan promosi pangan pokok non-beras sesuai potensi wilayah KTI, (2) Prioritas kebijakan di bidang pangan dan gizi di wilayah KTI perlu diarahkan kepada penduduk pedesaan dan kelompok pendapatan rendah, (3) Memenuhi tingkat konsumsi energi dan protein bagi kelompok rumah tangga berpendapatan rendah di daerah pedesaan diperlukan peningkatan pendapatan sekitar 2 persen, dan (4) Sosialisasi pendidikan dan penyuluhan di bidang pangan dan gizi masih sangat diperlukan.